Electrochemiluminescence Detection of Sunset Yellow by Graphene Quantum Dots - Niu, Huimin; Yang, Xin; Wang, Yilei; Li, Mingchen; Zhang, Guangliang; Pan, Peng; Qi, Yangyang; Yang, Zhengchun; Wang, John; Liao, Zhenyu (Frontiers in Chemistry, 2020)
Food additives, such as colorants and preservatives, are highly regulated because of their potential to human health risks. Effective detection of these compounds is, thus, very important to the conformation of industry standards and reduction in risk. In this paper, we details a study on the preparation and performance of an ultrasensitive, electrochemiluminescence (ECL) sensor for detection of a key food additive, sunset yellow. The sensor makes use of graphene quantum dots (GQDs) as the luminescent agent and potassium persulfate as the co-reactant. Strong and sensitive ECL signals are generated in responding to trace amounts of sunset yellow added. A detection limit (signal to noise = 3) of 7.6 nM and wide linear range from 2.5 nM to 25 μM are demonstrated. A further advantage is that the luminescent reagents can be recycled, which shows their sustainable nature, in addition to being simple and highly sensitive.